Cognitive and Experienced Flexibility in Patients With Anorexia Nervosa and Obsessive Compulsive Disorder - Sternheim, Lot Catharina; van Passel, Boris; Dingemans, Alexandra; Cath, Danielle; Danner, Unna Nora (Frontiers in Psychiatry, 2022)
Objective: Anorexia nervosa (AN) and Obsessive-Compulsive Disorder (OCD) share a neuropsychological profile characterized by cognitive inflexibility as evident in set-shifting problems, and by weak central coherence. The aim of this comparative study was to explore aspects of these problems in individuals with AN with those with OCD and a control group (HC). Method: 200 participants (61 AN, 72 OCD and 67 HC) performed neuropsychological tasks on set-shifting abilities (Trail Making Task, Stroop color-word interference, Intradimensional-Extradimensional shift task), on detail focus (Group Embedded Figures Test) and self-reported set-shifting abilities and attention to detail (DFlex). Results: Reduced set-shifting ability was only found on the Trail Making Task and similar between the clinical groups. Detail focus was weaker for both clinical groups compared to HC. Patients self reported more set-shifting problems but a less strong detail focus than HC, which in turn were not related to neuropsychological task outcomes. Conclusion: Cognitive inflexibility processes appear similar in patients with AN and OCD. Both patient groups report inflexibility, yet this is unrelated to neuropsychological outcomes. Findings highlight the need for entangling different domains of cognitive flexibility and central coherence and examining self-report measures for a cohesive understanding of clinically relevant flexibility weaknesses in AN and OCD.